How The Behavioral Intentions of SME Actors: The Relationship Between Financial Literacy and Financial Knowledge With the Mediating Role of Attitude - Nunuk Latifah; Shanti Ike Wardani; Sulistya Dewi Wahyuningsih (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aimed to explore and understand the behavioral intentions of micro and small business owners in Blitar regarding the use of financial application services. Data were collected using a census sampling technique through an online questionnaire, employing a 5-point Likert scale. A total of 135 respondents, all micro and small business actors in the Blitar area, participated in the survey. Data were processed using SEM-PLS. The results of the study revealed that business actors' actions in managing finances, financial knowledge, and financial literacy do not have a significant influence on behavioral intentions. The behavioral intentions of business actors are still relatively low in determining attitudes, knowledge, and understanding of financial management. This is primarily because their focus lies in marketing and sales. Even though many possess strong financial knowledge, their attitude tends to prioritize managing finances in ways that enhance production, promotion, and market expansion through digital platforms. On the other hand, financial literacy was found to positively influence both financial attitudes and financial knowledge. Financial attitudes can shape investment decisions, especially when supported by financial literacy, which enhances the ability to manage finances and make informed investment choices. Nevertheless, financial literacy does not serve as a moderating factor between financial behavior and financial attitudes in business decision-making